(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
Throughout his professional career as a journalist, Giuseppe Fava (1925-1984) developed an ethical conception of journalism as a social force capable of preventing and fighting social injustice. A very similar ethics found expression in his intellectual activities as a novelist, playwright, screenwriter and documentarian. Through an analysis of Alien Sciascia, the ironic portrait that Fava made of his most famous and respected contemporary, Leonardo Sciascia, this article aims to provide insight into Fava’s literary ethics and poetics, as well as into his interpretation of the intellectual’s function within society and in the fight against organised crime. What emerges is a call for intellectuals to act as involved inter-generational bridge figures who have witnessed and critically analysed the tragic consequences of mafia violence and oppression in the decades following World War II without giving in to feelings of hopelessness or cynicism. Keywords: Giuseppe Fava, anti-mafia movement, critical consciousness, intellectual commitment, Leonardo Sciascia